Video-Based Laboratories in Physics: A Quasi-Experimental Study on Rotational Dynamics and Critical Thinking Enhancement - Romadhon, Dzikri Rahmat; Muslim, M Adam Buchori; Suwarna, Iwan Permana (Jurnal Pijar Mipa, 2024)
This study aimed to evaluate the effectiveness of Video-Based Laboratories (VBL) in enhancing critical thinking skills among state Islamic senior high school (Madrasah Aliyah Negeri) students in Hulu Sungai Tengah, Kalimantan Selatan, specifically in the context of rotational dynamics. Using a quasi-experimental design, we compared the performance of an experimental group that utilized VBL with a control group that followed traditional teaching methods. Data were collected through pretest and posttest assessments on critical thinking skills, and various statistical analyses were performed, including the paired samples t-test, Wilcoxon signed-rank test, and Mann-Whitney U test. The findings indicated significant improvements in critical thinking skills for both groups; however, the experimental group demonstrated substantially greater gains. This suggested that VBL, through interactive and hands-on learning methods, effectively enhanced critical thinking skills in physics education. The results underscored the potential of integrating VBL into physics curricula to foster deeper understanding and reflective reasoning. Future research should explore the long-term impacts of VBL and its application in diverse educational settings.